Impact of comorbidity and frailty on prognosis in colorectal cancer patients: a systematic review and meta-analysis - Boakye, Daniel; Hoffmeister, Michael; Brenner, Hermann (Cancer treatment reviews, 2018)
INTRODUCTION: Colorectal cancer (CRC) is largely diagnosed at old age, when comorbidities and frailty are common and might be important prognostic factors of CRC. We aimed to systematically review epidemiological evidence on the prognostic role of comorbidity and frailty in CRC patients. METHODS: We systematically searched the PubMed and Web of Science databases up to August 08, 2017 for observational studies that used a standardized index to assess comorbidity or frailty, investigated and reported odds ratios (OR) or hazard ratios (HR) of their associations with any of the following CRC prognostic outcomes: thirty-day, overall or CRC-specific mortality and disease-free or recurrence-free survival. The study was conducted using standard meta-analysis methodology. RESULTS: Thirty-seven cohort studies were identified and included in this review: 35 on comorbidity and 2 on frailty. Of the 35 studies, 13 with comparable methodology were eligible for a meta-analysis. Compared to CRC patients without comorbidity, those with mild/moderate and severe comorbidity had, respectively, a higher risk of 30-day (OR=1.71; 95% confidence interval (CI): 1.26-2.31 and OR=2.62; 95% CI: 1.97-3.47), overall (HR=1.41; 95% CI: 1.23-1.62 and HR=2.03; 95% CI: 1.76-2.34), and CRC-specific mortality (HR=1.06; 95% CI: 1.02-1.10 and HR=1.14; 95% CI: 1.04-1.23). Frail CRC patients showed higher overall mortality than non-frail patients (HRrange: 2.60-3.39). CONCLUSIONS: Comorbidity and frailty are strong prognostic factors of survival in CRC patients apart from the commonly considered sociodemographic and tumor characteristics. Comprehensive geriatric assessment might help to optimize care of CRC patients, by improving early identification and management of comorbidities and geriatric syndromes.